Implementasi Lesson Study dalam Pembelajaran Matematika Kelas VI SD Negeri Karyasari 1 Menggunakan Pendekatan Model Pembelajaran Matematika Realistik (Penelitian Tindakan Kelas) - Chandra Sagul Haratua; Neneng Tanjihah; Elva Maulidia; Ahmadi Hasbie Asmariana; Kiki Nur Azizah (Universitas Palangka Raya, 2024)
This study aims to explore the implementation of Lesson Study with the Realistic Mathematics Education (RME) approach in teaching mathematics to sixth-grade students at SD Negeri Karyasari 1. The method of classroom action research was employed to observe two cycles of teaching, involving planning, implementation, and evaluation of lessons. Data were collected through observation, interviews, and analysis of student learning outcomes. The results of the study indicate that the application of the RME approach within the Lesson Study framework can enhance students' understanding of mathematical concepts, improve learning motivation, and strengthen collaboration among teachers. This research provides valuable insights into the effectiveness of this instructional approach in the context of primary education.